Associations between tobacco smoking status and patch test results: a cross-sectional pilot study from the Information Network of Departments of Dermatology (IVDK) - Molin, Sonja; Brans, Richard; Bauer, Andrea; Becker, Detlef; Kreft, Burkhard; Mahler, Vera; Skudlik, Christoph; Stadler, Rudolf; Szliska, Christiane; Weisshaar, Elke; Geier, Johannes (Contact dermatitis, 2024)
Background Earlier studies suggested a potential association between tobacco smoking and nickel sensitization, but little is known about other contact allergens. Objectives To investigate the association of smoking status and contact sensitizations as well as subtypes of dermatitis, and to analyse the sensitization profiles of tobacco smokers. Patients and Methods Within the Information Network of Departments of Dermatology (IVDK), we performed a cross-sectional multicentre pilot study comprising 1091 patch-tested patients from 9 departments, comparing 541 patients with a history of cigarette smoking (281 current and 260 former smokers) with 550 never-smokers. Results We could not confirm the previously reported association between nickel sensitization and tobacco smoking. Moreover, sensitizations to other allergens, including colophony, fragrance mix I, Myroxylon pereirae and formaldehyde, were not increased in cigarette smokers compared with never smokers. Hand dermatitis (50.6% vs. 33.6%) and occupational cause (36.2% vs. 22.5%) were significantly more frequent among cigarette smokers compared with never-smokers as shown by non-overlapping 95% confidence intervals. Conclusions Although our study does not allow a firm conclusion on whether smoking status contributes to certain contact sensitizations, it confirms an association of smoking with hand dermatitis and occupational cause.